Answer:
2x² + 13x + 15
Step-by-step explanation:
| 2x | 3
x | 2x*x = 2x² | 3*x = 3x
5 | 2x*5 = 10x | 3*5 = 15
We have, 2x² + 3x + 10x + 15
Combining like terms, we would have the final expression as:
2x² + 13x + 15
G (x) = x + 1 (fog) (x) = x 2 + 3x + 1 ⇒ (fog) (x) = x 2 + 3x + 1 ⇒ f (g (x)) = x 2 + 3x + 1 ⇒ f (x + 1) = x 2 + 3x + 1 Eg x + 1 = p, then x = p - 1. ⇒ f (p) = (p - 1) 2 + 3 ( p - 1) + 1 ⇒ f (p) = p 2 - 2p + 1 + 3p - 3 + 1 ⇒ f (p) = p 2 + p - 1 So f (x) = x 2 + x - 1 - ->
ANSWER IS : x 2 + x - 1
The answer is -2.25 bye!!!!!!!!!!!!!!!!!!!!!!!!!1
the answer is 12.2 for 150 rounded to nearest tenth
Answer:
x=2(twice)
y=0(twice)
Step-by-step explanation:
This question can be solved using substitution method
So let's solve
y=x+2....(1)
y=x2+5x+6....(2)
Substitute (1) into(2)
X+2=x2+5x+6
Collect like terms
X2+5x-x+6-2=0
X2+4x+4=0
X2+2x+2x+4=0
X(x+2)+2(x+2)=0
(X+2)(x+2)=0
X+2=0
Substrate 2 from both sides
X=-2
X+2=0
X=-2
Let's substitute the value of x into (1)
y=x+2
y=-2+2
Y=0(twice)